2014
DOI: 10.1002/2013ja019364
|View full text |Cite
|
Sign up to set email alerts
|

Linear mode conversion of Langmuir/z mode waves to radiation: Averaged energy conversion efficiencies, polarization, and applications to Earth's continuum radiation

Abstract: Linear mode conversion (LMC) is the linear transfer of energy from one wave mode to another in a density gradient. It is relevant to planetary continuum radiation, type II and III radio bursts, and ionospheric radio emissions. This paper analyzes LMC by calculating angle‐averaged energy (ε) and power (εp) conversion efficiencies in both 2‐D and 3‐D for Langmuir/z mode waves (including upper hybrid waves for perpendicular wave vectors) converting to free‐space radiation in turbulent plasmas. The averages are ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The waveforms are observed near or at the magnetopause, where there are gradients in n e and | B |, making linear mode conversion a possible source of radio emission. Previous observations and theoretical studies suggest that the magnetopause may be a source of nonthermal continuum radiation in the magnetosphere (Jones, ; Kurth et al, ; Schleyer et al, ). What instabilities are responsible for the observed waves? How do the unstable electron distributions develop, and therefore, under what magnetospheric conditions do the waves develop?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waveforms are observed near or at the magnetopause, where there are gradients in n e and | B |, making linear mode conversion a possible source of radio emission. Previous observations and theoretical studies suggest that the magnetopause may be a source of nonthermal continuum radiation in the magnetosphere (Jones, ; Kurth et al, ; Schleyer et al, ). What instabilities are responsible for the observed waves? How do the unstable electron distributions develop, and therefore, under what magnetospheric conditions do the waves develop?…”
Section: Discussionmentioning
confidence: 99%
“…The waveforms are observed near or at the magnetopause, where there are gradients in n e and |B|, making linear mode conversion a possible source of radio emission. Previous observations and theoretical studies suggest that the magnetopause may be a source of nonthermal continuum radiation in the magnetosphere (Jones, 1987;Kurth et al, 1981;Schleyer et al, 2014 This suggests that temperature anisotropy, ring distributions, or weak loss cones of the hot magnetospheric electrons are possible sources of instability. Such distributions can also be unstable to whistler waves, which would account for why whistlers are often observed simultaneously with UH and Bernstein waves (e.g., Figure 7).…”
Section: 1002/2017ja025034mentioning
confidence: 99%
“…In this weak turbulence frame, several conversion mechanisms are presently debated to explain the EM emission. EM decay or coalescence ( L → T f ± S ), where a Langmuir wave L decays into an EM wave T f close to the plasma frequency and an ion wave S , and linear mode conversion on density gradients (Schleyer et al, and references therein) are the most advocated mechanisms to explain the emission at T f . Regarding the emission at the harmonic, three main processes are proposed which all involve the presence of a current at 2 f p in the plasma: (i) a two‐step process involving Langmuir decay instability (LDI; Kruer, ) also called Langmuir electrostatic decay, followed by a coupling of electrostatic waves; LL+S1em1em1emL+LT2f …”
Section: Introductionmentioning
confidence: 99%
“…This type of mode conversion has been observed in warm plasma simulations [ Kim et al , , , ] and could be the source of the bursty MF waves observed by Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions at approximately 700 km [ Broughton et al , ]. In the context of the mode conversion of upper hybrid waves, Schleyer et al [] simulated mode conversion for a large range of parameters and found that for ionospheric conditions, the angle‐averaged energy mode conversion efficiency from the upper hybrid mode to the one of the electromagnetic modes ranged from ∼10 −10 to 10 −3 . The simulation results presented in Figure are consistent with the idea that the mode conversion efficiency on the topside is low, even though these simulations were run at a temperature higher than that of the ionosphere.…”
Section: Discussionmentioning
confidence: 83%